2018
DOI: 10.1186/s12917-018-1374-7
|View full text |Cite
|
Sign up to set email alerts
|

Virulence gene profiles: alpha-hemolysin and clonal diversity in Staphylococcus aureus isolates from bovine clinical mastitis in China

Abstract: BackgroundStaphylococcus aureus, a common cause of bovine mastitis, is known for its ability to acquire to antimicrobial resistance and to secrete numerous virulence factors that can exacerbate inflammation. In addition, alpha-hemolysin has an important role in S. aureus infections, diversity of the hla gene (that produces alpha-hmolysin) in S. aureus isolated from bovine mastitis has not been well characterized. The objective was, therefore, to determine diversity of virulence genes, hla gene sequences, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 46 publications
4
41
1
1
Order By: Relevance
“…Resistance of Staph. aureus was lower in our study than previously reported in China (Shi et al, 2010;Wang et al, 2015;Zhang et al, 2018a), whereas resistance data for Staph. aureus were similar to that reported by others (Rajala-Schultz et al, 2004;Güler et al, 2005).…”
Section: Discussioncontrasting
confidence: 88%
“…Resistance of Staph. aureus was lower in our study than previously reported in China (Shi et al, 2010;Wang et al, 2015;Zhang et al, 2018a), whereas resistance data for Staph. aureus were similar to that reported by others (Rajala-Schultz et al, 2004;Güler et al, 2005).…”
Section: Discussioncontrasting
confidence: 88%
“…Except for the seb gene that was detected in one isolate (S33). In contrast, Zhang et al () reported that some ST97 isolates had seb, sec and see genes. Meanwhile, Li et al () reported that no enterotoxin gene was present in ST97 isolates.…”
Section: Discussionmentioning
confidence: 92%
“…Similar results were found in Italy by Magro et al () who reported that clfA , clfB , epbS and vwb genes were harboured by all S. aureus strains isolated from bovine mastitis cases. In China, Zhang et al ( ) reported that more than 85% of S. aureus isolated from bovine mastitis cases harboured clfA , clfB , fnbA , and fnbB genes. However, differences were observed in the prevalence of fnbA and fnbB genes in isolates from Australia, where Gogoi‐Tiwari et al () reported that 54·5% of isolates harboured the fnbA gene and only 1·3% of S. aureus strains harboured the fnbB gene.…”
Section: Discussionmentioning
confidence: 99%
“…Different pathogenic properties require different detection methods, both for disease treatment and for gene identification [2]. To successfully treat this pathogen, it is essential to identify and characterize the virulence gene profiles and the clonal diversity present in S. aureus isolates [24].…”
Section: Role Of Staphylococcus Aureus Toxic Proteins In Mastitismentioning
confidence: 99%